2018
DOI: 10.1088/1674-1056/27/11/117502
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline and nanocomposite permanent magnets by melt spinning technique

Abstract: The melt-spinning technique offers an opportunity for tailoring magnetic properties by controlling the structures and microstructures in both single-phase and composite magnets. This review first broadly discusses the principle of cooling control, amorphization, crystallization, annealing, and consolidation of the melt-spun ribbons. The phase, microstructure, and magnetic properties of popular single-phase nanocrystalline magnets are reviewed, followed by the nanocomposite magnets consisting of magnetically ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 285 publications
1
17
0
2
Order By: Relevance
“…We found that GHN-2 exhibits a higher H c (6.1 kOe) and larger squareness S (≈0.8) than both the GHN-1 and HS (Figure 3a), confirming our simulation results (Figure 1c,d); moreover, GHN-2 shows the nature of magnetic isotropy, which is characterized by magnetic measurements parallel and perpendicular to the ribbon surface (Figure S5, Supporting Information), due to randomly oriented Nd 2 Fe 14 B grains within the material (Figure 2j). As a result, GHN-2 achieves a rare combination of high H c and high remanent magnetization (B r ) compared with previously reported isotropic Nd 2 Fe 14 B/α-Fe nanocomposite magnets (Figure 3b), [13,[29][30][31][32][33][34][35] and thus yields a record-high maximum energy product of (BH) max = 26 MG Oe (Figure 3c) for this class of isotropic nanocomposite magnets, which usually have values of ≈20 MG Oe. [4,6,17] The obtained energy product is ≈50% higher than that of the gradient-free counterpart (17.3 MG Oe) and outperforms the values of state-of-the-art isotropic permanent magnets.…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…We found that GHN-2 exhibits a higher H c (6.1 kOe) and larger squareness S (≈0.8) than both the GHN-1 and HS (Figure 3a), confirming our simulation results (Figure 1c,d); moreover, GHN-2 shows the nature of magnetic isotropy, which is characterized by magnetic measurements parallel and perpendicular to the ribbon surface (Figure S5, Supporting Information), due to randomly oriented Nd 2 Fe 14 B grains within the material (Figure 2j). As a result, GHN-2 achieves a rare combination of high H c and high remanent magnetization (B r ) compared with previously reported isotropic Nd 2 Fe 14 B/α-Fe nanocomposite magnets (Figure 3b), [13,[29][30][31][32][33][34][35] and thus yields a record-high maximum energy product of (BH) max = 26 MG Oe (Figure 3c) for this class of isotropic nanocomposite magnets, which usually have values of ≈20 MG Oe. [4,6,17] The obtained energy product is ≈50% higher than that of the gradient-free counterpart (17.3 MG Oe) and outperforms the values of state-of-the-art isotropic permanent magnets.…”
Section: Resultsmentioning
confidence: 55%
“…The observed directional magnetization reversal is unattainable in the existing systems due to a random distribution of low anisotropy regions (e.g., defects). [ 7,17 ] Although previously reported melt‐spun nanocomposite magnets [ 13,32–34 ] should have a structural gradient to some extent, the gradient effect may be too weak to significantly enhance the energy product, like GHN‐1 in Figures 3b and 4b. As such, the gradient impact on magnetic properties has not been revealed so far.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations